Application of the Spirometer and Oximeter Telemedicine Smartphone System in Lung Health Examination of Fish Smoking Workers in the Kenjeran Community Health Center working area - Ariswati, Her Gumiwang; Hari Wisana, I Dewa Gede; Luthfiyah, Sari; utomo, bedjo (Frontiers in Community Service and Empowerment, 2025)
The Community Service Program, in conjunction with the PKM scheme, is implemented through synergistic collaboration between the Surabaya Ministry of Health Polytechnic and the Surabaya City Health Service, focusing on community independence through counseling and assistance, particularly in the use of tools. Implementation of the Use of Spirometers and Oximeters Telemedicine Smart Phone System in Lung Health Examinations -Lungs of fish smoking workers in the Kenjeran Community Health Center work area. In connection with the increase in patients with cases of respiratory problems in the Kenjeran Community Health Center area, Surabaya City, as well as cases of respiratory problems in post-COVID-19 patients, which has resulted in a lack of treatment for these patients due to limited health personnel and no monitoring equipment. insufficient, so that the health service system for patients is disrupted. The use of a spirometer with a telemedicine smartphone system is expected to help people in Indonesia, especially in the Surabaya city area, to conduct early examinations independently and provide this information to medical personnel if any readings fall outside the specified parameters. This activity is an application of research following the road map (Road map Research), which has been carried out starting in 2019 to design an Apnea monitor to detect respiration rate in babies and adults using Piezoelectric sensors. Until 2024, it has been developed with a spirometer and oximeter with a telemedicine smart phone system and has been published in the journal IJEEMI, 2024, with the title Design and Development of an IoT-based Pulmonary Function and Oxygen Saturation Measurement Device (Pulmonary Function Analysis). In this activity, 21 fish smoking workers in the Kenjeran Community Health Center work area were examined using a spirometer and an oximeter smartphone telemedicine system carried out by the Team. Resulted in lung function measurements with FEV1/FVC ratio values, 86% normal and 14% restrictive